Case Report: Ivonescimab in EGFR-mutant lung cancer with baseline malignant pleural effusion and acquired complex resistance - Mo, Zeming; Jiang, Honglian; Zhou, Lei; Ren, Qiaoya; Shen, Gang; Li, Lie; Jian, Xiaobin; Yang, Hua; Bai, Yuju; Meng, Mi; He, Sisi (Frontiers in Immunology, 2025)
BackgroundPatients with epidermal growth factor receptor (EGFR)-mutant lung adenocarcinoma (LUAD) presenting with malignant pleural effusion (MPE) at diagnosis have a poor prognosis. Options are limited after EGFR-TKI resistance. Ivonescimab, a PD-1/VEGFA bispecific antibody, is effective in advanced non-small cell lung cancer, but its efficacy in patients with baseline MPE and complex acquired resistance remains unclear.Case presentationA 55-year-old man was diagnosed with LUAD and significant MPE, featuring an EGFR exon 19 deletion and over 20 co-mutations. The patient eventually developed resistance to both first-line gefitinib and later almonertinib. Repeat genomic testing of pleural fluid upon progression revealed persistent alterations in 12 genes, including the original EGFR sensitizing mutation, TP53, AKT2, RARA, and SETD2, alongside newly acquired mutations in CHEK1, CUL3, DNMT1, HMCN1, and TBX3, and RB1 copy number loss, in the absence of typical resistance mechanisms such as T790M or MET amplification or histologic transformation to small cell lung cancer. PD-L1 expression on the effusion cell blocks was positive (TPS 40%, CPS 41). He received ivonescimab monotherapy, achieving disease control for nearly 5 months before transitioning to ivonescimab plus pemetrexed with continued benefit and a manageable safety profile.ConclusionThis case illustrates the potential benefit of ivonescimab in patients with EGFR-mutant LUAD and baseline MPE who develop complex, non-canonical resistance to EGFR-TKIs. These findings support further clinical evaluation of ivonescimab in this poor-prognosis subgroup and highlight the importance of repeated molecular profiling in guiding treatment strategy.